Optimization of Post-Annealing NH3 Temperature for GaN Growth on GaAs (100) Substrate via Electron Beam Evaporator - Taib, M. lkram Md; Zainal, N.; Hassan, Z. (2015)
In recent years, gallium nitride (GaN) films have been widely grown by molecular beam epitaxy (MBE) and metal organic chemical vapour deposition (MOCVD). However, both are expensive techniques and require high maintenance and operation. Therefore, a more simple and cost-effective technique like electron beam (e-beam) evaporator should be more explored for growing GaN layer. So far, only few groups have work on this technique. In this work, we aim at demonstrating growth of GaN films on gallium arsenide (GaAs) substrate by ebeam evaporator. Our initial observation found that the GaN films lack the N atom component. Thus, the samples were annealed in ammonia (NHJ) ambient, and the annealing temperature was varied at 650 oc, 700 oc, 800 oc, 850 °C, 900 °C, 950 °C and 980 °C. The effects of using different annealing temperature on the properties of the GaN films were investigated through field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM). X-ray diffraction (XRD), photoluminescence (PL) and Raman spectroscopy. Towards the end, the optimum annealing temperature that promoted significant improvement to the GaN films is proposed.